FAKTOR YANG MEMPENGARUHI MINAT WANITA PREMENOPAUSE MELAKUKAN SRCEENING PAP SMEAR - Putri Damayanti, Ika; Maita, Liva (Ensiklopedia of Journal, 2025)
Cervical Cancer Cases in Indonesia in 2021 were 36,633 cases and were the second highest cause of death in women. Cervical cancer can be prevented in an easy and painless way, namely Pap Smear screening, which has a specificity of 91%. Pap Smear is an early detection of cervical cancer by taking fluid from the vagina to see abnormalities in cells around the cervix. Unfortunately, many women do not want to do Pap Smear, so the incidence of cervical cancer is high and when diagnosed, it immediately falls into a late and advanced stage. Data shows that the incidence of cervical cancer in people over 65 years of age is around 20%, and of all ages, the highest is in the 35-55 years of age. Fear, shame, and other factors cause the Pap Smear Screening coverage rate to be quite low. This study aims to determine what factors influence the interest of premenopausal women to do Pap Smear screening.  Based on the results of the study, it can be concluded that health information factors, knowledge level, and husband's role have a significant effect on the interest of premenopausal women in undergoing Pap Smear screening in the work area of Rumbai Health Center, Pekanbaru City. Meanwhile, economic level and education level factors did not show a statistically significant effect. It is recommended that health workers further improve health promotion regarding the importance of Pap Smear screening with methods that are more effective and easily understood by the community, especially those with low levels of education. There needs to be involvement of husbands in reproductive health education programs so that they can provide positive support to their wives. Further research with a wider scope and more diverse variables can be conducted to deepen understanding of the factors that influence interest in Pap Smear screening.Keywords   : Pap Smear, Cervical Cancer, Interest, Premenopause